Belief-based Stability in Coalition Formation with Uncertainty An Intelligent Agents$1 (BPerspective /s - Chan, Chi-kong.; Leung, Ho-fung.; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2013)
Belief-based Stability in Coalition Formation with Uncertainty An Intelligent Agents$1 (BPerspective discusses coalition stability. It extends the classic stability concept of the non-transferable utility core by proposing new belief-based stability criteria under uncertainty, and illustrates how the new concept can be used to analyze the stability of a new type of belief-based coalition formation game. The book is intended for graduate students, engineers, and researchers in the field of artificial intelligence and computer science. Chi-kong Chan is a laboratory manager and a visiting lecturer at the Hong Kong Polytechnic University, China; Ho-fung Leung is a Professor and the Chairman of Department of Computer Science and Engineering, The Chinese University of Hong Kong, China.s
Game Theoretic Analysis of Coalition Formation -- Strong Core and Weak Core -- b-Core -- An Example Application of the b-Core -- The Complete Picture$1 (Bthe sb-Core and the wb-Core.s
Keywords: Computer science; Algebra -- Data processing; Artificial intelligence; Mathematics; Computer Science; Artificial Intelligence (incl. Robotics).; Game Theory, Economics, Social and Behav. Sciences; Computers and Society; Symbolic and Algebraic Manipulation